Penerapan Model Pembelajaran Make a Match Untuk Meningkatkan Hasil Belajar IPA Kelas IV: (Studi pada SD Negeri 200405 Hutaimbaru Jl. Sibolga, Km 4 Hutaimbaru, Kec. Hutaimbaru, Kota Padangsidimpuan Prov. Sumatera) - Najmi Situmeang, Sabitah; Hilda, Lelya; Adinda, Anita (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research is motivated by the low learning outcomes of students in Natural Sciences. This is because the learning model applied is not optimal and students are less interested in the learning process. Therefore, it is necessary to change the implementation of learning in the classroom by using the make a match learning model (finding card pairs) in the learning process. The formulation of the problem in this study is how the application of the make a match model can improve the learning outcomes of grade IV science at SD Negeri 200405 Hutaimbaru Jl. Sibolga, KM 4 Hutaimbaru, Kec. Hutaimbaru, Padangsidimpuan City, North Sumatra Province. This study aims to determine the application of the make a match model can improve the learning outcomes of grade IV science at SD Negeri 200405 Hutaimbaru Jl. Sibolga, KM 4 Hutaimbaru, Kec. Hutaimbaru, Padangsidimpuan City, North Sumatra Province. The type of this research is Classroom Action Research (CAR) at the planning, action, observation and reflection stages at SD Negeri 200405 Hutaimbaru. The data collection instruments used were tests and observations. The results of the study showed that the application of the make a match model can improve student learning outcomes. This is evidenced by the increase in the average value and completeness of student learning outcomes, namely in the pre-cycle an average of 53.7% and completeness of 13% (3 out of 24 students). In cycle I, meeting I, the average score of student scores was 60.2% and student completeness was 39% (5 out of 24 students). While cycle I, meeting II, the average score of student scores was 72.5% and student completeness was 50% (12 out of 24 students). In cycle I, meeting I, the average score of student scores was 79.1% and student completeness was 71% (17 out of 24 students). While cycle II meeting II became the average score of student scores 92.9% and student completion 92% (22 out of 24 students). It can be concluded that the application of the make a match learning model can improve the learning outcomes of grade IV science at SD Negeri 200405 Hutaimbaru. For further research, the researcher hopes that the learning process will be further improved in order to achieve learning objectives, and the time is extended in the application of the make a match learning model